Penghinaan Terhadap Presiden dan Wakil Presiden Dalam KUHP Baru - Aprilianti, Della; Usman, Usman (Faculty of Law, Universitas Jambi, 2024)
The purpose of this study is to find out and analyze the regulation against insults against the president and vice president in the new Criminal Code and the old Criminal Code that has been declared unconstitutional by the Constitutional Court as well as to know and analyze the urgency of the insult article against the president and vice president so that it is revived. The formulation of the problem in this study is: 1) How is the regulation of the criminal act of insult against the President and Vice President in the Criminal Code? And 2) What is the criminal law policy on the urgency of the article of insult to the president and vice president so that it is included in the new criminal code? This thesis is written using a normative juridical type of research, which includes the study of norm vagueness. This thesis uses various approaches, including the Legislation approach, conceptual approach, comparative approach, historical approach. The results of the study found that 1) The regulation on insults to the President and Vice President in the new Criminal Code, is not a violation or defiance of the Constitutional Court Decision Number 013-022 / PUU-IV / 2006 because there is progress from regulating the criminal act of insult to the President and Vice President in the new Criminal Code 2) special protection of the dignity and dignity of the honor of the President and/or Vice President is something that deserves attention in a presidential system like Indonesia because the Criminal Code is considered no longer able to support various cases and dimensions of the development of new forms of crime. The Criminal Code, which is a Dutch heritage, is also seen as incompatible with the development of thoughts or ideas and aspirations, demands or needs of the community, both on a national and international scale.